Ambulatory Blood Pressure Monitoring and Echocardiographic Findings in Renal Transplant Recipients. Issue 8 (22nd December 2015) - Kendirlinan Demirkol, Ozlem; Oruc, Meric; Ikitimur, Baris; Ozcan, Sevgi; Gulcicek, Sibel; Soylu, Hikmet; Trabulus, Sinan; Altiparmak, Mehmet Riza; Seyahi, Nurhan
Abstract : Hypertension is common in renal transplant recipients (RTRs). Ambulatory blood pressure (BP) monitoring (ABPM) is important in diagnosing hypertension and diurnal BP variation. The authors set out to compare office BP and ABPM measurements to determine diurnal pattern and to evaluate echocardiographic findings in RTRs. ABPM and office BP measurements were compared in 87 RTRs. Echocardiographic evaluation was performed for each patient. The correlations between office and 24‐hour ABPM were 0.275 for mean systolic BP ( P =.011) and 0.260 for mean diastolic BP ( P =.017). Only 36.8% had concordant hypertension between office BP and ABPM, with a masked hypertension rate of 16.1% and white‐coat effect rate of 24.1%. Circadian BP patterns showed a higher proportion of nondippers (67.8%). Left ventricular mass index was increased in 21.8% of all recipients. There was a significant but weak correlation between office BP and ABPM.